Development and validation of high-performance liquid chromatography assay method for simultaneous determination of Caffeic acid, Vanillin, and Cinnamic acid in Algerian propolis extract - TOUTOU, Zahra (Biopolymer Applications Journal, 2025)
Propolis is a natural bee substance and resinous material produced from various plants, which showed important biological activities. The current study aims to evaluate and validate simultaneous methods of identification and quantification of three phenolic compounds (caffeic acid, vanillin, and cinnamic acid) in propolis extract from different Bejaia regions using high performance liquid chromatography (HPLC). Chromatographic analyses were performed using gradient mode, in are versed-phase C-18 (150 x 4.6 mm, 5 μm) column. The mobile phase contained 0.5% v/v acetic acid in water (solvent A) and acetonitrile (solvent B), using a flow rate of 1 ml/min and by injecting 20 μl, at a wavelength of 290 nm. The method was validated according to ICH guidelines. Specificity, linearity, accuracy, precision, detection, and quantification limits studies were made. The results showed that the correlation coefficient (R2) was > 0.99 for Caffeic acid, Vanillin, and Cinnamic acid, the percentage of relative standard deviation (RSD) of all assays found below 2% and 5% for intra-day and inter-day, respectively, limits of detection were 0.024, 0.008, and 0.009 mg/ml and limits of quantitation was 0.074, 0.025, and 0,029 mg/ml, for Caffeic acid, Vanillin, and Cinnamic acid respectively. According to these various parameters: accuracy, precision, linearity, and specificity, the proposed method was successfully validated in the simultaneous assay of Caffeic acid, Vanillin, and Cinnamic acid.